Legal Uncertainty in Fasum Land Disputes in Sampang Regency: Ketidakpastian Hukum dalam Sengketa Tanah Fasum di Kabupaten Sampang - Assyadillah, Muhamad; Khilmatus , Zhilda (Indonesian Journal of Law and Economics Review, 2024)
General Background: Land disputes over public facility (fasum) areas frequently arise due to conflicting claims, impacting legal and social stability. Specific Background: In Sampang District, a dispute emerged over fasum land in the "Puri Matahari" housing area, where a private individual constructed commercial buildings, conflicting with local regulations. Knowledge Gap: Inconsistencies in legal decisions and administrative weaknesses contribute to uncertainty in public land management. Aims: This study examines the legal status of the disputed land, judicial inconsistencies, and regulatory challenges while proposing governance improvements. Results: The findings confirm that the land legally belongs to the public domain, though administrative flaws led to legal disputes. Conflicting court rulings highlight the complexities of enforcing land use regulations. Novelty: This study identifies gaps in regulatory enforcement and judicial interpretation, proposing reforms to prevent similar conflicts. Implications: Strengthening legal frameworks, land administration, and judicial consistency is crucial to safeguarding public land and preventing future disputes. Highlights: Legal Ambiguity: Conflicting court rulings reveal gaps in public land regulations and enforcement. Administrative Weakness: Poor documentation and oversight contribute to disputes over public land use. Policy Reform Needed: Strengthening legal frameworks and governance can prevent future conflicts. Keywords: Land Dispute, Public Facility Land, Legal Uncertainty, Judicial Inconsistency, Land Governance